Continuous Glucose Monitoring Effects on Maternal Glycemic Control and Pregnancy Outcomes in Patients With Gestational Diabetes Mellitus: A Prospective Cohort Study - Yu, Fan; Lv, Lijuan; Liang, Zhijiang; Wang, Yi; Wen, Jiying; Lin, Xiaohong; Zhou, Yuheng; Mai, Caiyuan; Niu, Jianmin (The journal of clinical endocrinology and metabolism, 2014)
Context:Clinical evidence on the consequential effects of continuous glucose monitoring (CGM) on pregnancy outcomes in women with gestational diabetes mellitus (GDM) is scarcely available.Objective:Our objective was to evaluate the effectiveness of CGM on maternal glycemic control and pregnancy outcomes in patients with GDM .Patients:In total, 340 Chinese pregnant women with GDM were allocated to either the routine care group (n = 190) or the CGM group (n =150).Design and Setting:This was a prospective cohort study in the Department of Obstetrics of GuangDong Women and Children Hospital in China. Recruitment started in April 2011 and stopped in August 2012.Interventions:A 72-hour CGM system was used as a supplementary tool for glucose monitoring in the CGM group.Primary Outcome Measurements:The parameters of glycemic variability included mean blood glucose, the SD of blood glucose, mean amplitude of glycemic excursions (MAGEs), and the mean of daily differences. The maternal outcomes (preeclampsia and cesarean delivery) and composite neonatal outcomes were analyzed.Results:The SD of blood glucose, MAGEs, and mean of daily differences values were significantly lower in the CGM group compared with those of the routine care group (P < .001). Subjects in the CGM group were at lower risk of preeclampsia and primary cesarean delivery compared with the routine care group (P < .05). The mean infant birth weight of women in the CGM group was lower than infants of women in the routine care group (P < .001). The MAGE was associated with birth weight (β = 0.196, P < .001), and it was an independent factor for preeclampsia (odds ratio, 3.66; 95% confidence interval 2.16–6.20) and composite neonatal outcome (odds ratio, 1.34; 95% confidence interval 1.01–1.77).Conclusions:The use of supplementary CGM combined with routine antenatal care can improve the glycemic control and pregnancy outcomes of patients with GDM.